Study of Saving and Credit Mobile Application Model and Empowering the Poor - Margareta Wahyu Catur Wijayanti (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This study tries to describe how an application, called ASCA (Accumulating Saving & Credit Association) developed its mobile application on the Android platformfor empowering the poor. Microfinance has an important role in alleviating poverty, reducing income inequality and increasing economic growth. Community access to the formal financial system is only 52% of the total population, informal 31% and 17% of the population experience exclusivity unable to access the financial system. Based on the high level of poverty and the low access of the public to the financial system, WVI developed a savings group model, which is ASCA. Build upon monitoring and focused the discussion, the ASCA model proves to be a learning tool for the poor to save money, be disciplined to manage family finances, build good character of the borrower and change behavior in spending money. The application overcomes the weaknesses of manual recording, builds a transparent and independent information system, as well as records good financial footprint.